WED 258 Stroke mimic diagnoses on a centralised hyperacute stroke pathway. Issue 10 (13th September 2018) - Stefaniak, James D; Heartshorne, Rosie; Punter, Martin; Molloy, Jane
Abstract : Introduction: Stroke is highly prevalent, with an estimated 25.7 million occurring worldwide in 2013 1 . In an effort to reduce mortality and length of hospital stay 2, hyperacute stroke services have been fully centralised in Greater Manchester since 2015 such that all possible strokes within 48 hours of onset are transferred for assessment at one of three stroke centres. However, there have been concerns regarding the transfer of stroke mimic diagnoses along such pathways. Methods: A retrospective analysis was performed of patients assessed by the hyperacute stroke team in the Emergency Department of the Comprehensive Stroke Centre (Salford Hospital) in December 2015. Results: In December 2015, 309 patients with queried stroke were assessed by the Comprehensive Stroke Centre hyperacute stroke team. Of these, 82% had been redirected or transferred from another hospital. 47% had a non-stroke diagnosis at discharge or repatriation, resulting in a combined 331 days of stay at Salford hospital by patients without a stroke. The five most common non-stroke diagnoses were TIA, migraine, infection, seizure and functional neurological disorder. Conclusions: The optimal clinical care of non-stroke patients should be considered when planning centralisation of hyperacute stroke services. References: 1. Benjamin EJ, Blaha MJ, Chiuve SE, et al . (2017). Heart disease and stroke statistics-2017 update: A report from the American Heart Association. Circulation 135:0. doi:10.1161/CIR.0000000000000485 2. Morris S, Hunter RM, Ramsay AIG, et al . Impact of centralising acute stroke services in English metropolitan areas on mortality and length of study: Difference-in-differences analysis. BMJ 2014;349:4757.